Efforts to Improve Mathematics Learning Outcomes Determining FPB and KPK Class IV SDN Baros 04 Using Factorization Table Media - Dwi Haryani (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This research was carried out with the aim of improving student learning outcomes for class IV mathematics at SDN Baros 04 with a factorization table prop on the material to determine the KPK and FPB. This type of research is classroom action research (CAR). The subjects were class IV students, totaling 20 students. This CAR design includes planning, implementation, observation (evaluation), and reflection. Data collection techniques using observation and tests. Data analysis used quantitative descriptive statistics. The results showed an increase in learning outcomes in each cycle. During the pre-cycle the average value of 59.50 with the percentage of completeness (30%) increased during the first cycle to 67.75 the percentage of completeness (60%) and increased again in the second cycle with an average value of 80.50 the percentage of completeness (90%). Thus, it can be concluded that the use of factorization table props on the material to determine GCF and KPK can improve student learning outcomes.